Spiritual Intelligence and Its Relation to Depression Among Eleventh and Twelfth Grades Students of Nizwa in Sultanate of Oman - Al-Qassabi, Khalifa Ahmed Humaid; Al Buraidi, Naila Mahmood Amur (Journal of Educational and Psychological Sciences, 2020)
This study aimed at addressing the relationship between the spiritual intelligence and depression for eleventh and twelfth grades students of Nizwa in Ad-Dakhiliyah Governorate. The study sample included (350) male and female students chosen randomly. The researcher used “King” inventory (2008) of spiritual intelligence translated by Al-Kiumi and Al-Furaisiyah (2018), and the inventory of Arabic depression list for children made by Abdul-Khaliq (1991). The researcher used the descriptive correlative approach. The results showed a high level of spiritual intelligence and low level of depression among the study sample students. There were also statistically significant differences in the level of spiritual intelligence in favor of females, and there was no significant difference in the level of depression except for the dimensions of (lack of focus and pessimism, and self-hatred) in favor of males. The study concluded that spiritual intelligence contributes to reduction of depression by (23.9%). 1. The researchers recommended a set of recommendations, the most important of which are: the use of the depression reduction equation reached by the research, when building counseling programs, and developing spiritual intelligence through curricula and teaching to protect students from depression.
Keywords: Spiritual Intelligence; Depression; Nizwa state